Psychological Profile, Competitive Anxiety, Moods and Self-E cacy in Beach Handball Players - Reigal-Garrido, Rafael Enrique; Vazquez Diz, Juan Antonio; Morillo Baro, Juan Pablo; Hernández-Mendo, Antonio; Morales-Sánchez, Verónica Odilia (MDPI, 2020)
The first objective of this research was to analyze the relationships between the sports psychological profile, competitive anxiety, mood and self-e cacy in beach handball players. The second objective was to determine the predictive capacity of the psychological profile on competitive anxiety, moods and self-e cacy, which was assessed by linear regression analysis. One hundred and eighty-one beach handball players participated in this research (age: M = 25.68; SD = 5.95), of which 52.49% were male (n = 95) and 47.51% were female (n = 86). The Psychological Sports Execution Inventory (SPPI), the Competition Anxiety State Inventory 2 (CSAI-2), the Mood Profile (POMS) questionnaire and the General Self-Efficacy Scale (GSES) were used to obtain the data. Correlation and linear regression analyses reveal statistically significant associations between the constructs studied, both for the total sample and by gender. Specifically, they highlight the relationships between the di erent measures of the sports psychological profile with self-confidence (p < 0.001), as well as those established between negative coping control with competitive anxiety (p < 0.001), moods (p < 0.05) and general self-efficacy (p < 0.001).
Keywords: Ejercicio físico - Aspectos psicológicos; psychological profile; sports performance; team sport